Hindu religious art and architecture - Ghosh, Sankar Prosad, 1938- (D.K. Publications ; distributed by D.K. Publishersʼ Distributors, 1982)
Study of the impact of Vaishnavism on the art and architecture of medieval Bengal; with special reference to the Hindu temples in Nadia District.